PENINGKATAN KREATIVITAS SISWA MELALUI PERMAINAN CIPTA LAGU DALAM PEMBELAJARAN SENI BUDAYA DI SMK NEGERI 1 BENAI - Yasrizal Indri (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Riau, 2018)
This research is based on the result of Art Culture Study of Vocational Secondary School of Negeri 1 Benai which isstill very low and less interesting. This study aims to improve the learning result of Art Culture and studentcreativity. From data analysis of research result, there is improvement both from cycle I to cycle II, and cycle II tocycle III. Namely on the cycle element indicator of the song I get 8% percentage, in the second cycle increased to48%, and the third cycle increased to 55%. For the indicator of creativity also increased both from cycle I, II and IIIthat in cycle I get 0% presentation after cycle II increased to 8%, and after cycle III increased to 48%. For studentmotivation indicator, get presentation in cycle I of 2%, after cycle II to 33%, and cycle III increased to 62%. Thus itcan be concluded, improving the creativity of students through songwriting games in Cultural Art learning canimprove student learning outcomes and creativity on the subjects of Art Culture at Vocational Secondary School 1Benai.